The Routledge Handbook of Translation and Media - Bielsa, Esperança (Taylor & Francis, 2022)
Translation history and literary translation, on the one hand, and periodical publications, on the other, have been extensively analysed within the fields of translation studies, comparative literature, and media studies, with numerous conferences and publications taking literary translation and the periodical as objects of enquiry. However, the relationship between both fields still remains underexplored and nationalistic approaches and disciplinary boundaries have precluded the development of further conceptual and methodological insights regarding literary translation and the media. This chapter highlights the innovative theoretical and methodological issues intrinsic to analysing literary translation in periodical publications at both small and large scales, whether using or not digital tools, and sheds light on its qualitative implications for research. To do so, we briefly present a case study related to the Spanish-speaking world's literary journals at the beginning of the twentieth century.